Learning on the wires : BYOD, embedded systems - Longo, Brunella (2013)
Aims to identify and define some of the legal issues, computer misuses and information misbehaviour associated with IT security that are increasingly matters for civil litigation, criminal cases and national policy where fighting serious organised crime and cybercrime are concerned.